Assessment of Predictors of Mortality in COVID-19 Patients Treated with Tocilizumab - M. Asim Rana, M. Ahad Qayyum, M. Hasan Siddiqui, R. Omer Siddiqui, M. Waseem, M. Javed, R. Pervaiz, M. Mansoor Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A hypersensitivity condition called cytokine storm is the main cause of death in COVID-19 patients. A monoclonal antibody called tocilizumab may be able to suppress the Interleukin-6 receptors (IL-6R) and lessen the likelihood that the body would have a hypersensitive immune response. Aim: To evaluate the mortality advantages of tocilizumab in individuals with COVID-19. Study design: Retrospective study. Place and duration of study: Bahria Town International Hospital Lahore from 16th June 2020 to 17th September 2021. Methodology: Patients with 96 confirmed instances of COVID-19 were enrolled. Two groups of patients were created. A single dosage of tocilizumab was administered to 52 participants in the first group, referred to as the survivors, and 44 patients in the second group, who passed away within 14 days. From the patients' medical records, the demographic information, co-morbid conditions, and laboratory values were obtained. The hospital's institutional review board and ethics committee (IRBEC) gave its approval for this study. The permission was ignored because this was a retroactive analysis. Results: 54.24 16.58 was the average age, and 54 (56.25%) of the population were men. 52 (54.16%) patients were survivors, compared to 44(45.83%) patients in the non-survivor group. In non-survivors compared to survivors, the older age group was shown to be statistically significant (62.78±12.86 vs. 51.65±11.68, p=0.003). Additionally, non-survivors had a greater BMI (p=0.006). In our study, hypertension and diabetes were the two co-morbid conditions that were most frequently detected (35.24% and 28.94%, respectively). The mortality rates among patients with diabetes, asthma, COPD, and cancer were all considerably higher (P=0.01, 0.006, and 0.004, respectively). Cancer and type-2 diabetes patients had death rates that were considerably higher (p=0.05 and p=0.01, respectively). C-reactive protein (CRP), D. Dimer, procalcitonin (PCT), and IL-6 were discovered to be the significant predictors of mortality (p 0.0001, 0.05, 0.001, and 0.004 respectively). Conclusion: Even though tocilizumab is authorised and has been shown to have positive results, people with diabetes, COPD, and asthma are more likely to experience negative results even after getting a single dosage of the medication. Similar to CRP, D. Dimer levels are reliable indicators of death. Keywords: Tocilizumab, Motility predictors, Co-morbid conditions, COVD-19, Procalcitonin, D. Dimer